Beranda perdamaian : Aceh tiga tahun pasca MoU Helsinki - Bhakti, Ikrar Nusa (Yogyakarta : Pustaka Pelajar, 2008)
Political and social conditions of Aceh after the implementation of Helsinki MoU
'Dokumen dan undang-undang': p. 398-399
Includes bibliographical references (p. 385-398) and index
Keywords: Nanggroe Aceh Darussalam (Indonesia) -- Politics and government -- 21st century; Nanggroe Aceh Darussalam (Indonesia) -- Social conditions -- 21st century